PATHOGENESIS OF COLLETOTRICHUM LINDEMUTHIANUM THE INCITANT OF ANTHRACNOSE DISEASE IN BEANS MEDIATED BY MACERATING ENZYMES - MOHAMMED FAISAL PEERAN; PRABAKAR KUPPUSAMI; RAGUCHANDER THIRUVENGADAM (The Bioscan, 2014)
Bean anthracnose, caused by the fungus Colletotrichum lindemuthianum (Sacc. & Magnus) Lams Scrib., is a serious seedborne disease of common beans (Phaseolus vulgaris L.). Anthracnose has caused serious reductions in the yield of beans in many parts of the world, resulting in yield losses as high as 95%. Plant cell wall contains mainly cellulose and pectic substances which offers first line of defense. Macerating enzymes secreted by pathogens are involved in the pathogenicity of a wide range of plant pathogenic fungi. In the present study all isolates of C. lindemuthianum were able to grow in synthetic medium and produce cellulolytic (C1 and Cx). The maximum activity was observed in CL 06 (0.94 and 80.12%) respectively. Polymethylgalacturonase (PMG), polygalacturonase (PG) and pectin lyase (PL) activities were detected. The isolate CL06 produced higher amount of PG and PMG (0.47 and 0.91), similarly the isoaltes CL06 (153.26) showed higher activity of pectate lyase. All the enzymes were highly active in 12-day-old culture and the activities decreased with the increase of culture age. Isolate CL 06 yielded high titles in production of all the enzymes.